A STRUCTURAL EQUATION MODELLING APPROACH TO VALIDATE QUESTIONNAIRE PEER LEARNING USING CONCEPT CARTOON - Yin, Khoo Yin; Bing, Khuan Wai; Yusof, Hamidah; Zakariya, Zainizam; Karim, Noor AlHuda Abdul (PEOPLE: International Journal of Social Sciences, 2016)
Institutions of higher education are facing new challenges in improving their quality of teaching nowadays. Educators believe that effective and quality teaching depend on strategies. Sense of humour is always classified as one of the important element for effective teaching. Concept cartoons have integrated a sense of humour, concept and daily life that can make the lesson more interesting and lively. The purpose of this paper is to validate the questionnaire by using confirmatory factor analysis. The questionnaire was answered by 392 secondary school students in Malaysia. Structural Equation Modelling was applied to test the model. The results confirmed that the revised model has achieved the minimum requirement of the model fit. The overall goodness of fit of the model has improved. The findings also revealed the two factors (communication and interest) measurement were valid and reliable. Future research on this topic could be carried out with an animated cartoon series in various fields.